How can Asian hotel companies remain internationally competitive?. Issue 5 (13th July 2015) - Lam, Carmen; Ho, Grace K.S.; Law, Rob
Abstract : Purpose: – This paper aims to examine a number of Asian hotel companies to identify the hurdles and provide recommendations for those companies expanding internationally. Many Asian-based hotel companies have made their strategic choice to expand beyond their home territories by opening and managing hotels in non-Asian destinations to achieve growth. This is a strategic decision that other Asian hotel companies will eventually have to face when they follow their customers' footsteps and/or enhance their brand awareness in non-Asian destinations for greater market penetration and other network advantages. Design/methodology/approach: – This is a review article that analyzes Asian hotel groups' development practices based on content analysis of published references. The 2012 Hotels 325 list, the leading source of news and analysis for the global hotel industry, is used to identify the top Asian hotel management companies in the world. Their history is traced to examine key success factors for their growth and to identify issues and concerns for such companies' development into non-Asian destinations. Findings: – There are a number of approaches that Asian hotel companies have adopted for international expansion based on their match with these companies' key success factors. Research limitations/implications: – The review focuses on the top 53 Asian hotel companies on the Hotels 325 list and does not cover smaller Asian companies that may have had successful global expansion records. Practical implications: – The paper provides high-level guidelines for what Asian hotel groups need to do to expand their business internationally outside of Asia or their traditional markets. Non-Asian hotel groups would also learn from this Asian wave of hotel development. Originality/value: – There has been limited, if ever any, previous literature on the strategic development choices of Asian hotel management companies. As such, this paper contributes to such an important but largely overlooked area in hotel management.